Pengaruh Penggunaan Website pada Materi Keanekaragaman Hayati Berbasis Hasil Riset Terhadap Kemampuan Literasi Konservasi Siswa SMP Kelas VII - Roihanah Fatin; Suroso Mukti Leksono; Adi Nestiadi; Septi Kurniasih (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2025)
This study aims to determine the effect of using a website on biodiversity material based on research results on students' conservation literacy skills. The method used is a quasi-experimental design with a nonequivalent control group design. Students' conservation literacy skills were measured through three indicators: cognitive (using pretest and posttest questions), affective (using an attitude questionnaire), and psychomotor (assessed through a poster assignment). In this study, the experimental class used the EDUKASI website, while the control class used PowerPoint. The results showed that the use of the website had an effect on students' conservation literacy skills. This was evidenced by the hypothesis testing using a t-test at a significance level of 0.05 for each indicator: cognitive (Sig. 0.001), affective (Sig. 0.000), and psychomotor (Sig. 0.000). Thus, H₁ is accepted and H₀ is rejected, indicating that the use of a research-based website influences the conservation literacy skills of seventh-grade junior high school students. Keywords: Biodiversity, Conservation Literacy Skills, Website